Diseño, implementación y evaluación de un sistema de biofiltración con lombrices (eisenia foetida) para el tratamiento de aguas residuales provenientes de la críanza de cerdos en la propiedad de la familia lima ubicada en el barrio playas la florida, cantón Yantzaza provincia de Zamora Chinchipe - Lima Coronel, José David (2016)
The current investigation was developed in Playas La Florida neighborhood, Yantzaza canton, the purpose was to design and build a natural ecological system of replicable pilot bio filtration of residual water treatment, as a natural treatment, sustainable and low-cost alternative to reduce contaminating of fresh water cannels and thereby ensure the health o population and protection of the environment. First, it was started with the revision of the literature to substantiate and clear the concepts regarding the subject studied. Secondly, the characterization as the direct observation of the study site, interview the landowner. Then the physic, chemical and bacteriological of residual water characterization was done and the flow rate that is generated daily in the swinish was determined through the volumetric method of gauging, obtaining as a result a residual water that does not vary according to the time of the washing of the swinish. Then through the use of mathematical equations the dimensions of the settler, fat trap and bio filtration system were determined, which were constructed of cyclopean concrete with a block of sand. To prove the percentage of decontamination of the natural treatment, a sample of treated residual water was collected and a laboratory analysis was made, reaching a high percentage of depuration in fats, oils and suspended solids with 92.57% and 90% respectably. Likewise Chemical Oxygen Demand and Biochemical Oxygen Demand with a purification percentage of 88.17% and 86.71% respectively. For this reason finally concluding to be a suitable system to purify the residual waters from the rearing of pigs.